Evangelicalism & the future of Christianity - McGrath, Alister E., 1953- (London: Inter Varsity Press, 1995)
Alister McGrath's confidence in evangelicalism is infectious, moving his readers to believe with him that this movement may "hold the key to the future of Western Christianity." But McGrath is aware of evangelicalism's weaknesses, especially its lack of appreciation for history and its own spiritual heritage. He proposes, then, ways for the movement to address its weaknesses and capitalize on its strengths.
1. The Evangelical Renaissance -- 2. Evangelical Distinctives -- 3. The Appeal of Evangelicalism -- 4. A Loss of Vision? Evangelical Expansion & a Crisis of Identity -- 5. The Quest for an Evangelical Spirituality -- 6. The Dark Side of Evangelicalism -- 7. Evangelicalism & the Future of Christianity.
Includes bibliographical references (pages 191-209).
Keywords: Evangelicalism; Evangelicalism -- History; Christianity -- 20th century